Enhancement of body red coloration in juvenile spotted scat (Scatophagus argus) by dietary supplementation with Lianjiang red orange peels as a natural carotenoid source - Han, Tong; Liao, Yongguan; Yang, Lei; Li, Xinyi; Shi, Gang; Jiang, Dong-Neng; Zhu, Chunhua; Li, Guangli; Shi, Hongjuan (Frontiers in Marine Science, 2024)
Spotted scat (Scatophagus argus) is an economically important marine species in China, with high ornamental and edible value. The effects of dietary supplementation of Lianjiang red orange peels, a natural carotenoid source, at 0, 3, 6, 9 and 12%, hereafter referred to as G0, G3, G6, G9 and G12, were measured on color values, carotenoid content, expression of genes such as cyp2j6, cyp1a1, hsp70, slc2a11, bco2, cyp26c1 after 4 weeks. Subsequently, the different color values (L*, a*, and b*), total carotenoids content, and gene expression pattern were analyzed. In the groups fed diets containing more than 9% Lianjiang red orange peels (9% and 12%), the L* value (lightness) decreased, while the a* value (redness) increased in red skin, and b* value (yellowness) increased in caudal fin (P < 0.05). Additionally, the total carotenoids content in red skin of the G9 group and caudal fin of the G12 group was substantially higher than in the other groups (P < 0.05). By comparative transcriptome analysis of the red skin in G0 and G9 groups, 419 differentially expressed genes (DEGs) were identified, of which 237 were upregulated and 182 were downregulated. Genes involved in carotenoid deposition (cyp2j6, cyp1a1) and pigment cell development (hsp70, slc2a11) were significantly upregulated, whereas genes related to carotenoid decomposition (bco2) and retinoic acid metabolism (cyp26c1) were significantly downregulated in the G9 group. These findings suggest that Lianjiang red orange peels, as a natural carotenoid source, enhance body coloration by influencing the deposition of carotenoid, pteridine pigments, erythrophore development, and inhibiting the oxidative cleavage of carotenoid and retinoic acid metabolism. This study enhances body coloration by influencing carotenoid and pteridine pigment deposition, and provides theoretical guidance for aquaculture practices involving spotted scat.